Penguatan Pendidikan Karakter di Sekolah Dasar di Era Revolusi Industri 4.0 - Zidniyati Zidniyati (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
The purpose of this study is to re-examine what is meant by character education, how to apply character education in several elementary schools, including methods and results, and to try to reformulate the appropriate character education model in the era of industrial revolution 4.0. The methodology of the study carried out in this paper is an analysis of studies from various sources of theory about character education and industrial revolution 4.0, and an analysis of studies of several character education practices carried out in several elementary schools / madrasah ibtidaiyyah (MI) in Banyuwangi region as well in the Jogjakarta Region. The results of the research from both the theoretical and of the practical analysis in this paper is that the application of character educationstill does not produce the results as expected. However, so far, there have been many elementary school level that have implemented character education according to the abilities of educator resources. Educator resources are the main determinant in achieving or not the goal of character education for each school that applies it, especially in terms of determining programs as a form of character education. It was also found that the results of character education applied to each school also varied, depending on how the educator's resources interpreted the objectives of the character education program in their respective schools.